Persistent arthralgia among Chikungunya patients and associated risk factors in Chennai, South India - Ramachandran, V; Kaur, P; Kanagasabai, K; Vadivoo, S; Murhekar, MV (Journal of postgraduate medicine, 2014)
Context: Chikungunya (CHIK) fever is viral disease characterized by joint pain for prolonged duration in various settings. However, there are no reports of long-term follow-up of the CHIK patients from India. Aims: We conducted a cohort study to describe the clinical manifestations, incidence of persistent arthralgia, and the associated risk factors among patients with CHIK identified during an outbreak in a suburb of Chennai, India. Materials and Methods: We conducted a retrospective cum prospective cohort study in Gowripet, Avadi, Chennai. We included all adult CHIK case patients identified during the outbreak. We conducted a nested case-control study to identify the risk factors for persistent arthralgia defined as a CHIK case experiencing arthralgia for more than 15 days from the date of onset of illness. We included all 81 patients and 81 randomly selected controls. Results: All 403 case patients had joint pain. Approximately 40% suffered joint pain for up to 1 month and 7% had it beyond 1 year. The most commonly affected types of joints were knee (96%), wrist (80%), and ankle (77%) joints. Regarding the number of types of joints affected, 36% had six types of joints, 23% had five types of joints, and 14% had three types of joints affected. The overall incidence of persistent arthralgia was 80%. High-grade fever, involvement of four or more types of joints, and joint swelling were significantly associated with persistent arthralgia. Conclusions: High prevalence of persistent arthralgia indicates the need for appropriate treatment strategies to reduce the severity and duration of joint pain.